Proportion and factors associated with severe zoonotic malaria infection in Pahang from 2011 until 2022 - Mokhtar, Tengku Muhammad Huzaifah Tengku (2024)
Introduction: Malaria remains a global public health challenge, with zoonotic malaria caused by the Plasmodium knowlesi parasite posing a significant threat in Southeast Asia, particularly in Malaysia. Severe zoonotic malaria, a disease stage characterized by life-threatening complications, is a major concern. This study aims to determine the proportion and factors associated with severe zoonotic malaria infection in Pahang, Malaysia, from 2011 to 2022. Methodology: This cross-sectional study utilized secondary data from the VEKPRO malaria database, including 487 zoonotic malaria cases reported in Pahang between 2011 and 2022. Descriptive statistics were employed to determine the proportion of severe cases of zoonotic malaria, while multiple logistic regression identified factors associated with severe infection of zoonotic malaria. Results: Among the 487 cases analyzed, 97 (19.9%) were classified as severe zoonotic malaria infections, and 390 (80.1%) were uncomplicated. Key factors significantly associated with severe infection included age, occupation, and delay in diagnosis. Individuals over 60 years old had a significantly higher risk of severe infection (Adjusted OR: 18.49, 95% CI: 2.17–157.59) compared to those under 15. Forest-related occupations were also a significant risk factor (Adjusted OR: 2.21, 95% CI: 1.32–3.71) compared to non-forest-related jobs. Additionally, a diagnosis delay of more than 4 days substantially increased the risk of severe zoonotic malaria (Adjusted OR: 5.18, 95% CI: 2.65–10.14). Conclusions: The high proportion of severe zoonotic malaria cases in Pahang underscores significant public health concerns. Critical risk factors such as older age, forest-related occupations, and delayed diagnosis require targeted public health interventions. Enhancing diagnostic facilities and ensuring prompt healthcare access, especially in rural areas, are crucial to reducing the severity of zoonotic malaria.